Two newly recorded species of Anthocerotophyta from Xizang, China - Zhuogabayong; SONG Xiaotong; HONG Jiakang; GU Jiqi; SHAO Xiaoming; WANG Ruihong (Xibei zhiwu xuebao)
[Objective] The study aims to understand the distribution of Anthocerotophyta in Xizang, add new materials for the research of moss plants in Xizang, and provide essential basic data for the conservation of bryophyte diversity in China. [Methods] The research materials of Anthocerotophyta were obtained from field investigation. The species diversity was determined through indoor morphological observation and literature review. [Results] The collected specimens of corneophytes, growing in the meadow at the edge of the spruce forest and autochthonism in Linzhi, were analyzed by classical taxonomic method combined with observation of the morphological structure of plant body and sporophyte. Two new records, Anthoceros punctatus L. and Phaeoceros laevis (L.) Prosk., were identified. [Conclusion] A . punctatus L.and P . laevis (L.) Prosk. were recorded for the first time in Xizang.